Skin Color and Identity Formation - Fergus, Edward (Latino Communities: Emerging Voices - Political, Social, Cultural and Legal Issues, 2005)
The focus of this study is on the ways in which skin color moderates the perceptions of opportunity and academic orientation of 17 Mexican and Puerto Rican high school students. More specifically, the study's analysis centered on cataloguing the racial/ethnic identification shifts (or not) in relation to how they perceive others situate them based on skin color.